Progressive Ataxia and Palatal Tremor: Think about POLG Mutations - Mongin, Marie (Tremor Other Hyperkinet Mov (N Y), 2016)
BACKGROUND: Progressive ataxia and palatal tremor (PAPT) can be observed in both acquired brainstem or cerebellar lesions and genetic disorders. PHENOMENOLOGY SHOWN: PAPT due to mutation in POLG, the gene encoding the mitochondrial DNA polymerase. EDUCATIONAL VALUE: POLG mutation should be considered in patients with PAPT, particularly when additional clues such as a sensory neuronopathy or an ophthalmoplegia are present.